2016
DOI: 10.2147/bctt.s121610
|View full text |Cite
|
Sign up to set email alerts
|

Expression and functionality of TRPV1 in breast cancer cells

Abstract: Transient receptor potential (TRP) channels contribute to the regulation of intracellular calcium, which can promote cancer hallmarks in cases of dysregulation of gene transcription and calcium-dependent pro-proliferative or anti-apoptotic mechanisms. Several studies have begun to elucidate the roles of TRPV1, TRPV6, TRPM8, and TRPC1 in cancer progression; however, no study has examined the expression profiles of human TRP channels in breast cancer on a large scale. This study focused on the expression and fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
81
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 42 publications
3
81
0
1
Order By: Relevance
“…TRPV6 had a high level of expression in breast adenocarcinoma tissue [87]. TRPV1 is functionally expressed in SUM149PT breast cancer cells, a model for a very aggressive form of breast cancer (i.e., triplenegative breast cancer) [88], and in MCF7 breast cancer cells [89,90].…”
Section: Transient Receptor Potential Channels In Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…TRPV6 had a high level of expression in breast adenocarcinoma tissue [87]. TRPV1 is functionally expressed in SUM149PT breast cancer cells, a model for a very aggressive form of breast cancer (i.e., triplenegative breast cancer) [88], and in MCF7 breast cancer cells [89,90].…”
Section: Transient Receptor Potential Channels In Breast Cancermentioning
confidence: 99%
“…TRPV1 seems to be one of the most promising TRP channels as a pharmacological target in breast cancer. To date, capsaicin inhibits cancer growth in SUM149PT breast cancer cells, by triggering apoptotic/necrotic mechanisms, while capsazepine diminishes these effects [88]. MRS1477, a positive allosteric modulator of TRPV1, when co-applied with capsaicin, diminished the fraction of MCF7 breast cancer apoptotic cells but was ineffective against tumor growth in MCF7 tumor-bearing immunodeficient mice [89].…”
Section: Trp Channels As Pharmacological Targets In Breast Cancermentioning
confidence: 99%
“…TRPV1 channel plays an important role in several physiological and pathological processes, such as nerve conduction, visceral pain sensing process [9,13,14], and activation of immunity [15]. Furthermore, a few studies shown previously that TRPV1 was likely involved in tumor progression [16], and its activation reduced cell proliferation, migration and invasion in breast cancer [17], urothelial cancer [18] and papillary thyroid carcinoma [19]. However, so far little is known about the role of TRPV1 channel in GI tumorigenesis, except Amaya G. et al reported that TRPV1 regulated neurogenic in ammation in the colon to presumably protect mice from colon cancer [20].…”
Section: Introductionmentioning
confidence: 99%
“…Ca 2+ signaling is crucial for tumor angiogenesis [5]. Ca 2+ influx directly modulates VEGF signaling, endothelial proliferation and angiogenesis [6].The expression of amount of Ca 2+ permeable transient receptor potential (TRP) channels is altered in many malignant tumors [7], such as TRPC1, TRPC3, TRPC6, TRPV1 and TRPV4 [8][9][10][11].Transient receptor potential vanilloid-3 (TRPV3), as one of the members of the TRP channels, we have demonstrated that TRPV3 was overexpressed in NSCLC and promoted proliferation of A549 and H1299 lung cancer cells. TRPV3 inhibition decreased intracellular calcium concentration ([Ca 2+ ] i ) of lung cancer cells and arrested cell cycle progression in G1/S boundary [12].…”
Section: Introductionmentioning
confidence: 99%